The impact of coaching advice on motor learning skills, with a particular focus on the role of self-competencies in high-performing athletes - Schröder, S. (Journal of Human Sport & Exercise, 2025)
In the context of competitive sports training, it is imperative that athletes receive regular training in self-competence to enhance self-regulation and self-control, thereby empowering them to actively influence their own learning process and mitigate stress. The present study (N = 35, mean age: 17.06) suggests a negative correlation between stress load and self-control (r = -.517, p < .001). Concurrently, a positive correlation was identified between self-control and willpower (r = .433, p < .005), with willpower also exerting an influence on motor learning, although not significantly (d = .358). The study set out to examine the hypothesis that the manner in which coaches communicate has a significant impact on motor learning (r = -.41, p < .005). Subsequent group comparisons revealed significant variations in juggling performance, which were associated with higher expressions of willpower (p = .027, d = .735). In comparison with the groups that achieved high self-competence scores, the group that received negative coach instruction and simultaneously exhibited a low level of self-competence demonstrated the poorest results in motor learning and exhibited significant differences to the athletes with high self-competence (p <= .020, d >= 0.75). These results underscore the significance of promoting self-competence in top athletes.